Stress Coping Behavior Of Workers Layoffs During The Covid-19 Living In Babalan District, Langkat Regency - Annya Tauzahra; Yara Andita Anastasya (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
This study aims to examine in depth about the stress coping behavior of workers who experience job cuts (layoffs) during COVID-19. This research uses a qualitative approach with case study methods. Selection of location and research subjects using purposeful sampling techniques. The subjects numbered three people, namely workers who experienced job cuts (layoffs) during the COVID-19 period who lived in Securai Village babalan district of Langkat regency. The data collection methods in this study used interviews, observations and documentation. The data analysis techniques used are data collection, data reduction, data display, and inference. The study also used all three triangulation of resources, technique, and time. The results of the Depression Anxiety Stress Disorder (DASS 42) questionnaire showed that all three subjects experienced mild stress with an assessment of roughly 18. The stress experienced by the three subjects in the form of sadness, upset, anxious, confused and discouraged when experiencing job cuts (layoffs). The results showed that all three subjects did the coping process, the first initial assessment, secondary assessment, and reassessment and decision. This aims to find out the cause of the problem that occurs, then the three subjects do stress coping. The three subjects used both forms of stress coping, namely problem focused of coping and emotion focused of coping. This can facilitate the process of handling the source of the problem that causes stress. As for a new findings from all three research subjects, the concept of self that affects coping stress is physical, social, moral and psychological